Cohesion in text: a systemic functional analysis of Chimamanda Ngozi Adichie's fiction - Koussouhon, Léonard; Allagbe, A. Ayodele (My University, 2014)
Abstract
Keywords: Cohesion; internal structure; patterns of meaning; text.